Child Infectious Morbidity in the USSR during the World War II (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: infectious child morbidity; child tuberculosis morbidity; the second world war (the great patriotic war 1941-1945); children2019; s evacuation